Independence day - Ford, Richard, 1944- (New York : Vintage Books, 1996)
Like most people Frank Bascombe, of New Jersey, a divorced realtor, has plans for the Fourth of July weekend: finds a new home for a client, see his semi-girlfriend, and take his son to a sports hall of fame. Instead, one disappointment follows another, but he takes them in his stride--philosophically. By the author of the Sportswriter.
Maine author.
Keywords: Real estate agents -- New Jersey -- Fiction; Fathers and sons -- New Jersey -- Fiction; Divorced men -- New Jersey -- Fiction; New Jersey -- Fiction